Duck plague virus UL47 gene affects the release and cell-to-cell spread of the virus and its deletion strains can provide strong protection for ducks - Yuxi Cui; Siyu Chen; Mingshu Wang; Wei Zhang; Qiao Yang; Xumin Ou; Di Sun; Yu He; Bin Tian; Zhen Wu; Shaqiu Zhang; Juan Huang; et al. (Poultry Science)
Duck plague (DP) is an acute, febrile, septicemic infectious disease caused by duck plague virus (DPV). pUL47, which is encoded by the DPV UL47 gene, is a relatively abundant late tegument protein in virions, and its effects on the life cycle and virulence of viruses remain unclear. Herein, we generated UL47-deficient DPVs through a two-step Red recombination system and examined the effects of UL47 on the viral life cycle, virulence, and immune protection of UL47-deficient strains. The results showed that the deletion of the DPV UL47 gene affected the release and cell-to-cell spread of the virus, thereby reducing the efficiency of mature virion generation and further affecting the proliferation of the virus. The absence of the DPV UL47 gene significantly reduced the virulence of the virus but maintained immunogenicity and immune efficacy, thereby inducing the production of DPV-specific antibodies to resist strong attack by DP. These findings offer valuable insights into the functional characterization of the UL47 gene and the development of an attenuated vaccine based on this gene. Furthermore, this study provides a novel approach for the prevention and control of duck plague.